Applications of evolutionary computation. 19th European Conference, EvoApplications 2016, Porto, Portugal, March 30-April 1, 2016, Proceedings /: 19th European Conference, EvoApplications 2016, Porto, Portugal, March 30-April 1, 2016, Proceedings. Part I : (2016) - Unknown
No abstract available